The Ninth European Congress on Clinical and Economic Aspect of Osteoporosis and Osteparthritis Athens, Greece 18 - 21 Mac 2009 - Foo Leng, Huat (Pusat Pengajian Sains Perubatan, 2009)
The increasing life expectancy is known to be associated with a greater frailty of elderly people and with a number of chronic and degenerative diseases. Osteoporosis and its complications- especially hip fractures, represent, probably, one of the most frequent disease in western population. Given the increasing importance of the morbidity and mortality associated with hip fractures, it is fundamental to identify screening methods in order to prevent them appropriately. Op~ tim a! identification of high-risk individuals would he a simple questionnaire assessing easy-to-know information on patients, linked to hip fracture risk. The FRACTURE index is a model identifying variables that could be easily assessed in either clinical practice or by self-administration. This model was developed and validated by Black for the screening of risk factors among patients in the orthopedics clinical practice allowing important insights about patient 5-years probability of hip fracture occurrence (every 2 units of FRACTURE index there is about a two fold increase of 5-yrs hip fracture probability). The assessment tool is a set of seven key parameters that can be easily asked to a patient within the usual orthopedic practice: these parameters indude age, BMD T-score, fracture after age 50 years, maternal hip fracture after age SO, weight less than or equal to 57 kg, smoking status, and use of arms to stand up from a chair. We performed an epidemiological cohort study, evaluating the FRACTURE index among 8590 patients recruited in 145 Italian Orthopedics divisions. Among the overall patients recruited, 3497 had a recent hip fracture. About 80% of fractured patients had a FRACTURE index >8/15. Our epidemiological cohort study confirms the validity of FRACTURE score index assessment in a clinical setting to establish the hip fracture risk probability.